Determinants of non-compliance of public procurement regulations in Kenyan secondary schools - Migosi, Joash; Ombuki, Charles; Ombuki, Kennedy N.; Evusa, Zablon (Academic Journals, 2013)
Kenya’s public procurement and disposal Act of 2005 sets out clear rules and procedures for public procurement entities to follow; however this does not seem to be the case. This study sought to examine determinants of Non-compliance to the Public Procurement Regulations in Kenyan Secondary Schools. The study adopted a descriptive survey research. A sample of twelve (12) schools was utilized in this study from a population of thirty three (33) registered public secondary schools in Kitui Central District. The target population was the Public Secondary School Tendering Committees’ members; the suppliers and the principals of the twelve (12) Public Secondary Schools were adopted for this study. Stratified random sampling was adopted in this study. The tendering committees yielded 120 respondents, school principals were 12 and the total number of suppliers was 60. Structured self administered questionnaires, interview guides and document analysis were used in data collection. Findings in this study revealed that most respondents in this study were not familiar with the new procurement rules and regulations. There is need therefore for government and public institutions to lay emphasis on familiarization of the new procurement rules and regulations and to intensify continuous education among the procurement stakeholders in the public procurement process particularly at the secondary school level. Key words: Procurement, compliance, secondary schools, Kenya.